Control-oriented modelling and identification theory and practice - Lovera, Marco (Institution of Engineering and Technology, 2015)
The process of developing control-oriented mathematical models of physical systems is a complex task, which in general implies a careful combination of prior knowledge about the physics of the system under study with information coming from experimental data. This book presents state of the art methods and tools available within the systems and control literature to support control oriented modelling activities and to illustrate their usefulness by means of a number of case studies and applications.
Keywords: Automatic control -- Mathematical models.; System design.; Control theory.; System identification.; elektronické knihy; electronic books